2019
DOI: 10.1186/s12885-018-5255-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of uPA and PAI-1 tumor levels and 4G/5G variants of PAI-1 gene with disease outcome in luminal HER2-negative node-negative breast cancer patients treated with adjuvant endocrine therapy

Abstract: BackgroundThe aim of this study was to evaluate the prognostic potential of urokinase-type plasminogen activator (uPA) and plasminogen activator inhibitor type 1 (PAI-1) tumor tissue levels and examine the association between these biomarkers and classical prognostic factors in early node-negative luminal breast cancer patients. The clinical value of 4G/5G variants of PAI-1 gene was evaluated.Patients and methodsThis study involved 81 node-negative, estrogen receptor-positive and/or progesterone receptor-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Indeed, uPA and PAI-1 are among the most highly induced proteins in several migratory or invasive tumor cell types. Even though some studies failed to show a correlation between elevated levels of PAI-1 and poor clinical prognosis [ 100 , 101 , 102 ], PAI-1 has been established as one of the most reliable biomarkers and prognostic markers in many cancer types, including breast [ 103 , 104 , 105 , 106 ], ovarian [ 107 ], bladder [ 108 , 109 ], colon [ 110 ], renal [ 111 ] and non-small cell lung cancers [ 112 ].…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…Indeed, uPA and PAI-1 are among the most highly induced proteins in several migratory or invasive tumor cell types. Even though some studies failed to show a correlation between elevated levels of PAI-1 and poor clinical prognosis [ 100 , 101 , 102 ], PAI-1 has been established as one of the most reliable biomarkers and prognostic markers in many cancer types, including breast [ 103 , 104 , 105 , 106 ], ovarian [ 107 ], bladder [ 108 , 109 ], colon [ 110 ], renal [ 111 ] and non-small cell lung cancers [ 112 ].…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…Previous literature have indicated that SERPINE1 had pro-angiogenic, growth and migration stimulation and anti-apoptotic activity, all of which were targeted at promoting tumor growth, cancer cell survival and metastasis [ 18 ]. SERPINE1 has been proven to be the most reliable biological and prognostic marker for a variety of cancers, including breast cancer [ 19 – 21 ], ovarian cancer [ 22 ], bladder cancer [ 23 , 24 ], colon cancer [ 25 ], kidney cancer [ 26 ] and non-small cell lung cancer [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasminogen activator inhibitor-1 (PAI-1), also known as endothelial plasminogen activator inhibitor or serpin E1, is a protein that in humans is encoded by the SERPINE1 gene (de Faria et al, 2019). PAI-1 is a serine protease inhibitor that functions as the principal inhibitor of urokinase (uPA) and tissue plasminogen activator (tPA), activators of fibrinolysis and plasminogen (Jevric et al, 2019). The other PAI, PAI-2, is secreted by the placenta and only present during pregnancy.…”
Section: Introductionmentioning
confidence: 99%